2015
DOI: 10.1002/art.39129
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Exposure and Risk of Juvenile Idiopathic Arthritis

Abstract: Objective Susceptibility to juvenile idiopathic arthritis (JIA) is presumed to be determined by both genes and environment. However, the environmental factors remain largely unknown. The hygiene hypothesis suggests that exposure to siblings, as a marker of exposure to microbes in early life, may protect against the development of later immune disorders. Some prior evidence suggests this may also be true for JIA. The present study was undertaken to test this hypothesis in detail. Methods We conducted a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…Consistent with our data, a previous Australian clinic-based study showed that having any siblings (vs. none) was protective for JIA in (OR 0.46, 95% CI 0.28; 0.74, using clinic-based controls); a result slightly attenuated (OR 0.50, 95% CI 0.24; 1.02) when community controls were used [10]. An OR of 1.6 for JIA was observed in relation to being an only child in a Danish registry-based study [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our data, a previous Australian clinic-based study showed that having any siblings (vs. none) was protective for JIA in (OR 0.46, 95% CI 0.28; 0.74, using clinic-based controls); a result slightly attenuated (OR 0.50, 95% CI 0.24; 1.02) when community controls were used [10]. An OR of 1.6 for JIA was observed in relation to being an only child in a Danish registry-based study [19].…”
Section: Discussionsupporting
confidence: 91%
“…Proxy measures often used to assess this include maternal parity (a greater number of prior births being consistent with a greater number of older daycare- or school-aged siblings at home and greater possibility of early infection); infant birthweight, small size-for-gestational age, or gestational age (small, or preterm infants may be less resistant to infection), and mode of delivery (vaginal deliveries may more likely elicit a normal immune response due to early exposure to vaginal flora). The microchimerism hypothesis relates to maternal and/or sibling origin microchimerism (harboring of cells or DNA from another genetically distinct individual) from exchange of cells/DNA in utero from the mother or older siblings during gestation [10]. Microchimerism may potentially increase or decrease disease risk based on the specificity of the acquired genetic material from another individual [11], and some studies suggest that its presence may alter rheumatoid arthritis (RA) risk in women [1217] although we could locate no studies of this in JIA.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an Australian study of 302 JIA and 1,012 controls reported a 2.2-fold higher risk of JIA in singleton children as compared to children with at least one sibling, with a dose-dependent relationship observed. 63 This was also supported by a Norwegian study, which reported that singleton children had 1.6-fold higher risk of JIA 59 as compared to children with siblings. However, not all studies have observed the protective effect of contact with siblings.…”
Section: Other Environmental Factors Affecting Microbiota Colonizationmentioning
confidence: 64%
“…Bell et al reported that higher maternal parity was associated with a decreased risk for persistent oligoarticular JIA (OR 0.32, 95% CI 0.15‐0.71 for 4 + prior deliveries). Additionally, an Australian study of 302 JIA and 1,012 controls reported a 2.2‐fold higher risk of JIA in singleton children as compared to children with at least one sibling, with a dose‐dependent relationship observed . This was also supported by a Norwegian study, which reported that singleton children had 1.6‐fold higher risk of JIA as compared to children with siblings.…”
Section: Early Life Events and Jia Riskmentioning
confidence: 71%
“…The use of two well‐characterized cohorts with detailed information has allowed pooled analyses to be conducted, demonstrating the robustness of this association. Additionally, the availability of sibling date of birth to calculate cumulative sibling exposure in our study is relatively unique as this method has been applied in only a few other studies . Unfortunately, we did not have sCD14 measurement which might have provided a clearer understanding of the relationship between CD14 genetic variations, environmental exposure, and sensitization.…”
Section: Discussionmentioning
confidence: 99%